Fraud Diamond In Financial Reporting Fraud Detection with Audit Committee as A Moderation - Priambada, Arga; Holiawati, Holiawati; Ruhiyat, Endang (Pelopor Publikasi Akademika, 2023)
The purpose of this study was to determine the effect of fraud diamond using four proxies, namely Financial Target, Ineffective Monitoring, Auditor Change and Board of Directors Change on the detection of financial statement fraud and the influence of the audit committee relationship as a moderating variable. This study used a sample of 16 companies from the agricultural product sub-sector that were listed on the Indonesia Stock Exchange from 2017 to 2021. The data used is secondary data in the form of financial reports and annual reports of the sample companies. Hypothesis testing was carried out using a panel data linear regression model with eviews 12 software. The results of this study indicate that Financial Targets and Auditor Turnover have an effect on fraudulent financial reports, Ineffective Monitoring and replacement of directors have no effect on fraudulent financial statements. The audit committee was unable to moderate the influence of Financial Targets, Ineffective Monitoring, Auditor replacements, Directors replacement on fraudulent financial reporting